Religious Diversity and Conceptual Schemes: Critically Appraising Internalist Pluralism - Burley, Mikel (Sophia, 2019)
Is a philosophical theory needed to 'underwrite' attitudes of toleration and respect in a multicultural and religiously diverse world? Many philosophers of religion have thought so, including Victoria Harrison. This article interrogates Harrison's theory of internalist pluralism, which, though offering a welcome alternative to other theories, such as John Hick's 'pluralistic hypothesis', nevertheless faces problems. Questioning the coherence of the theory's account of how the existence of objects of worship can avoid being fully conceptual-scheme dependent, and raising doubts about its pretensions to promote interreligious harmony, I also critically discuss the common philosophical tendency to work with under-described and insufficiently analysed examples. What philosophy ought to be able to offer in relation to religious diversity, I propose, is attentiveness to nuances and particularities, thereby aiding religious understanding without the need for a general theory.